AGUAPÉ (Eichhornia crassipes) COMO BIOADSORVENTE DO CORANTE TURQUESA REMAZOL - Holanda, Carlos Alexandre (2010)
In this work, the root, stem and leaf of Eichhornia crassipes were used in preparing bioadsorbent for removal of the textile dye Remazol Turquoise, from its aqueous solution. The biomass of water hyacinth was crushed isolated and treated with a solution of nitric acid at 50°C, followed by five washes for extraction of soluble matter. After filtration, the samples were dried and sieved to a particle size between 44 to 210 μm. The pHzpc values of bioadsorbent (pH at zero point of charge) were estimated at 3.3, 3.1 and 3.4 for the root, stem and leaf, respectively. Kinetic studies were performed at pH 2, due in this value the efficiency of the dye removal was the best. The kinetic models of pseudo-first and second orders were applied at temperatures 10, 25 and 40°C, and the second order model (R2 > 0.98) was that best modeled the experimental data. The intraparticle diffusion model showed three linear segments, indicating the three stages of the adsorptive process. The adsorption isotherms were obtained by varying the dye concentration from 50 to 50 mg.L-1 in the range from 50 to 1000 mg.L-1. The Freundlich, Langmuir, Sips and multilayers adsorption isotherms models have been applied to fit the experimental data, and the Sips model was the best one. The thermodynamic parameters confirmed the spontaneity of all studied adsorptive processes, which are endothermics, but with increasing entropies. The low desorption of the dye at pH's 8 and 11 showed the high affinity between matrices and dye, and the relative difficulty of the dye recovery and consequently, the reuse of these bioadsorbents, by this route.